The future of clinical leadership: evidence for physician leadership and the educational pathway for new leaders. Issue 2 (21st June 2017) - Goodall, Amanda; Stoller, James K
Abstract : Until recently, the title 'physician leader' was rarely heard particularly in the UK. But that is changing. Doctors are being drawn into leadership and management more systematically. New educational opportunities are being tailored to the specific needs of doctors. The change towards physician leadership is being driven by research showing that leaders who are experts in the core business, such as doctors, are associated with improved organisational performance. This article summarises that evidence and then reviews what we have learnt about how best to train future physician leaders.